Prevention of nosocomial legionellosis by best water management: comparison of three decontamination methods. Issue 4 (August 2020) - Muzzi, A.; Cutti, S.; Bonadeo, E.; Lodola, L.; Monzillo, V.; Corbella, M.; Scudeller, L.; Novelli, V.; Marena, C.
SUMMARY: Background: Since 2000, the National Health System has adopted international guidelines for assessing Legionella spp. in hospital water systems. The control of water contamination by Legionella spp. is still a matter of research concerning the most effective method in preventing nosocomial infections. Aim: To compare three different decontamination methods by monitoring colony-forming unit count and number of hospital-acquired legionellosis cases. A secondary objective was to evaluate the long-term effects of the preventive measures on the water pipes. Methods: A protocol was developed for the selection of high-risk sampling sites and for the testing of three disinfection methods over the course of 19 years: hyperchlorination and thermal shock (period A, 2000–2005); copper–silver ionization (period B, 2006–2010); and integration of pre-filtering, filtering, pipe-protecting products, and remote control with chlorine dioxide (ClO2 ) (period C, 2011–2018). Findings: The use of shock disinfection and hyperchlorination led to a decrease in contamination level immediately after the procedure, but then it rose again to the previous level in two months. Both copper–silver ionization and ClO2 disinfection showed a stable and durable decrease in contamination level. Throughout these three phases, six cases of Legionella spp . occurred during period A, six cases during period B, and three cases during period C. With regard to the damage of water pipes, effective copper–silver levels caused corrosion and calcification in water pipes. Conclusion: Both copper–silver ionization and ClO2 properly controlled Legionella spp . contamination. ClO2 significantly reduced the number of positive sites ( P < 0.001) without damaging the pipelines.